KONTRIBUSI KECERDASAN EMOSIONAL TERHADAP SUBJECTIVE WELL-BEING SANTRI PUTRI ASRAMA TAHFIDZ PONDOK PESANTREN MUKHTAR SYAFA’AT BLOKAGUNG TEGALSARI BANYUWANGI - Mahmudah Mahmudah; Muhammad Imam Khaudli; Ahmad Qusyairi (JKaKa:Jurnal Komunikasi dan Konseling Islam, 2021)
Santri often feel bored, depressed, bored, and burdened until it finally affects the emotions and happiness of students. Subjective well-being is a scientific term that scientists use to describe happiness. In order to realize subjective well-being, there are factors that must be considered. This study aims to determine the effect of emotional intelligence on the subjective well-being of female students in the tahfidz dormitory of the Mukhtar Syafa'at Islamic Boarding School Blokagung Tegalsari Banyuwangi. This research approach uses a quantitative approach, while this type of research uses descriptive research. The research sample used purposive sampling method, the sample was taken only from female students of the Tahfidz dormitory. The results showed that there was a significant influence between emotional intelligence on subjective well-being of female students in the Tahfidz boarding school Mukhtar Syafa'at Islamic Boarding School Blokagung Tegalsari Banyuwangi with the effective contribution given by emotional intelligence to subjective well-being of 32.4%, while the rest were 67.6% influenced by other factors.